2011
DOI: 10.1242/dmm.006825
|View full text |Cite
|
Sign up to set email alerts
|

Swatting flies: modelling wound healing and inflammation in Drosophila

Abstract: Aberrant wound healing can lead to a variety of human pathologies, from non-healing chronic wounds that can become dangerously infected, to exuberant fibrotic healing in which repair is accompanied by excessive inflammation. To guide therapeutic intervention, we need a better understanding of the fundamental mechanisms driving tissue repair; this will require complementary wound-healing studies in several model organisms. Drosophila has been used to model genetic aspects of numerous human pathologies, and is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
79
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 54 publications
1
79
0
Order By: Relevance
“…An effect of wounding is also supported by the fact that genes in Wnt and hedgehog signaling, as well as components of the extracellular matrix, are enriched in our gene set. All three pathways have been shown to be important during wound healing acting at different stages in vertebrates and may play comparable roles in flies [37,38]. For example, the Wnt pathway may support the establishment of planar cell polarity during epidermal wound healing similar to its role during development and the extracellular matrix may play a role similar to the granulation tissue that forms after wounding in vertebrates [39].…”
Section: Discussionmentioning
confidence: 99%
“…An effect of wounding is also supported by the fact that genes in Wnt and hedgehog signaling, as well as components of the extracellular matrix, are enriched in our gene set. All three pathways have been shown to be important during wound healing acting at different stages in vertebrates and may play comparable roles in flies [37,38]. For example, the Wnt pathway may support the establishment of planar cell polarity during epidermal wound healing similar to its role during development and the extracellular matrix may play a role similar to the granulation tissue that forms after wounding in vertebrates [39].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical excision (Bryant, 1975;Haynie and Bryant, 1976;Katsuyama et al, 2015) or cell ablation induced by pro-apoptotic transgenes (Grusche et al, 2011;Herrera et al, 2013;Smith-Bolton et al, 2009) has revealed cellular responses that promote wound healing (Sun and Irvine, 2014;Kashio et al, 2014;Razzell et al, 2011). Disc size is restored by accelerated proliferation of cells proximal (Sustar et al, 2011;Bosch et al, 2008) and distal (Herrera et al, 2013) to the wound site.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, research has identified conserved mechanisms of wound healing in embryonic and larval animals. 9,10 However, the adult remains one of the last systems to be characterized for tissue repair and regeneration in Drosophila and poses a great opportunity to examine how genetic factors impact these processes independent of the roles they serve in developmental contexts.…”
Section: Introductionmentioning
confidence: 99%